Breakthroughs in satellite remote sensing of floods - J-P. Schumann, Guy (Frontiers in Remote Sensing, 2024)
Flooding is among the top-ranking disasters worldwide, evident through frequent and devastating events causing significant localized impacts and broader repercussions. Floods lead to substantial insured and uninsured losses, with a few hundred billions of $US in flood-related losses over the last 5 years, only a moderate amount of which were insured. Remote sensing, especially via satellite technology, has great potential for flood mapping and monitoring. Although many initiatives utilize satellites for flood response, few have resulted in operational protocols for mandated response organizations. Historic breakthroughs in satellite remote sensing have occurred since the 1970s, with six major milestones enhancing flood monitoring over the last half century. This article looks back at these technological development breakthroughs and the barriers to progress they lifted. Advancements in machine learning, cloud computing, and increased satellite missions promise more developments. Anticipated innovations include satellite constellations with various sensors and self-learning processing models to relay real-time insights for disaster response. Looking forward, a transformative shift in flood mapping from space may be expected as early as 2025, driven by enhanced orbital computing for predictive capabilities, improving disaster preparedness and response.